Patient Perspectives on the Hula Empowering Lifestyle Adaptation Study: Benefits of Dancing Hula for Cardiac Rehabilitation. Issue 1 (January 2015) - Maskarinec, Gregory G.; Look, Mele; Tolentino, Kalehua; Trask-Batti, Mililani; Seto, Todd; de Silva, Mapuana; Kaholokula, Joseph Keawe'aimoku
Background. The Hula Empowering Lifestyle Adaption Study, funded by the National Institute on Minority Health and Health Disparities, was a 5-year research trial evaluating the impact of the traditional Native Hawaiian dance form, hula, as an exercise modality for cardiac rehabilitation, compared with usual care, on individuals recently hospitalized for a cardiac event or who had recently undergone coronary artery bypass surgery. Method and results. Seeking to learn what physical, mental, spiritual, and social effects the intervention may have had for participants, we interviewed 20 of a total of 35 patients who were enrolled in the dance arm of the study. Classical thematic triangulation analysis was used. Participants recognized that hula's coordination of body, mind, and spirit as a group activity deepened their appreciation of and connections to Hawaiian culture. This was true for those who were Native Hawaiian, connecting to their own cultural heritage, as well as for non–Native Hawaiians, who found that it improved their appreciation of the surrounding cultural traditions of the host culture where they now live. Conclusions. Not only was hula a safe activity that improved functional capacity, participants also regarded its significant sociocultural aspects—even for participants who are not Native Hawaiian —as enhancing its value and meaningfulness. Learning the words of well-known Hawaiian songs provided additional long-term cues that encouraged "ownership" of the therapy and acted as practical reminders of the importance of exercise and lifestyle moderation while also offering new spiritual connections to the surrounding social environment.